Thermoresponsive and Photocrosslinkable Poly(2-alkyl-2-oxazoline) Toolbox - Customizable Ultralow-Fouling Hydrogel Coatings for Blood Plasma Environments - Wiesner Née Diehl, Fiona; Petri, Christian; Hageneder, Simone; Kunzler, Cleiton; Klees, Sven; Frank, Petra; Pertiller, Matthias; Dostalek, Jakub; Knoll, Wolfgang; Jonas, Ulrich (Macromolecular rapid communications, 2024)
This study focuses on developing surface coatings with excellent antifouling properties, crucial for applications in the medical, biological, and technical fields, for materials and devices in direct contact with living tissues and bodily fluids such as blood. This approach combines thermoresponsive poly(2-alkyl-2-oxazoline)s, known for their inherent protein-repellent characteristics, with established antifouling motifs based on betaines. The polymer framework is constructed from various monomer types, including a novel benzophenone-modified 2-oxazoline for photocrosslinking and an azide-functionalized 2-oxazoline, allowing subsequent modification with alkyne-substituted antifouling motifs through copper(I)-catalyzed azide-alkyne cycloaddition. From these polymers surface-attached networks are created on benzophenone-modified gold substrates via photocrosslinking, resulting in hydrogel coatings with several micrometers thickness when swollen with aqueous media. Given that poly(2-alkyl-2-oxazoline)s can exhibit a lower critical solution temperature in water, their temperature-dependent solubility is compared to the swelling behavior of the surface-attached hydrogels upon thermal stimulation. The antifouling performance of these hydrogel coatings in contact with human blood plasma is further evaluated by surface plasmon resonance and optical waveguide spectroscopy. All surfaces demonstrate extremely low retention of blood plasma components, even with undiluted plasma. Notably, hydrogel layers with sulfobetaine moieties allow efficient penetration by plasma components, which can then be easily removed by rinsing with buffer.
Keywords: krevní plazma; Alkynes; Humans; hydrogely; azidy; benzofenony; alkyny; lidé; polymery; Polymers; SPR/OWS; betaines; Plasma; Benzophenones; blood plasma; Hydrogels; antifouling thermoresponsive hydrogel coatings; photocrosslinkable poly(2-oxazoline)s; Azides